Operando plasmon resonance sensoring applied to sodium-ion batteries - Ewaldsson, Stefan (My University, 2022)
The sodium-ion storage mechanism in hard carbon was studied by the means of nano-plasmonic resonance spectroscopy. The measurements were made operando, using a gold nano-film deposited onto an optical fiber which was inserted into a battery half cell, cycled at different C-rates. The most favourable sensor type was also investigated. It was found that correlation between the optical signal and voltage signal was possible. The fast cycles in the cycling regime used, led to capacity fade, which can be seen to mainly affect the plateau region of the discharge voltage signal. This could be explained by the more sluggish diffusion of intercalated sodium-ions in the hard carbon structure. The first cycle of the cells showed a unique response in the optical spectra, suggesting that the fiber is sensitive to events during formation cycles, such as the solid electrolyte interphase formation.
Keywords: Nano-plasmonic sensing; Na-ion; Hard carbon; Na-ion storage mechanism; Fiber optical battery sensing